Digital Transformation of Deed Printing Services Through the Population Administration Information System (SIAK) at the Population and Civil Registration Office of Badung Regency - Mareta, Komang Vriska Tiara; Wirantari, I Dewa Ayu Putri (West Science Information System and Technology, 2025)
The digitization of population administration services has become an urgent need to enhance the effectiveness and efficiency of public services in today’s information technology era. The Population Administration Information System (SIAK) implemented in Badung Regency demonstrates significant changes in the process of printing certificates and other population documents, with technology utilization that facilitates access and accelerates service completion. The implementation of various innovations such as the integrated service package “Badung Aku Sapa” and the mobile service “Go Laying Adminduk” has successfully increased inclusivity and convenience for the community in managing population administration, especially for vulnerable groups such as the elderly and people with disabilities. Efforts to develop smart villages and the implementation of Digital Population Identity (IKD) further strengthen service access down to the village level, reducing geographical and social barriers. However, this digital transformation process also faces various challenges, ranging from limited network infrastructure, low digital literacy among some communities, to data security issues and cultural resistance to new technology. Addressing these challenges through strengthening human resources, community education, and the development of reliable security systems are important aspects in supporting the sustainability of digitization in population administration services. Overall, the implementation of SIAK in Badung Regency illustrates an effective and inclusive model of public service digitization, which can serve as a reference for other local governments in optimizing modern and sustainable population administration services.